2017
DOI: 10.1177/1065912917702499
|View full text |Cite
|
Sign up to set email alerts
|

Gender Linked Fate, Race/Ethnicity, and the Marriage Gap in American Politics

Abstract: In this study, we explore the predictors of gender linked fate with a focus on marital status for different racial/ethnic groups. We argue that marriage alters women’s perceptions of self-interest by institutionalizing their partnerships with men and consequently leading women to feel less connected to other women. We assess our hypothesis using the 2012 American National Election Study. While we find that married white women and Latinas have significantly lower levels of linked fate than unmarried women of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 61 publications
(78 reference statements)
5
52
0
Order By: Relevance
“…Thus, it is no surprise that the Southern states–Missouri, Georgia, Kentucky and Mississippi–clustered in their passage of restrictive abortion laws in 2019 [30]. Here, we show that perceptions of gender linked fate–or seeing one’s future as linked to other women–helps explain support for legal abortion, extending existing research linking gender linked fate to conservative political attitudes [31].…”
Section: Introductionsupporting
confidence: 70%
“…Thus, it is no surprise that the Southern states–Missouri, Georgia, Kentucky and Mississippi–clustered in their passage of restrictive abortion laws in 2019 [30]. Here, we show that perceptions of gender linked fate–or seeing one’s future as linked to other women–helps explain support for legal abortion, extending existing research linking gender linked fate to conservative political attitudes [31].…”
Section: Introductionsupporting
confidence: 70%
“…It is possible that denying linked fate with the group is an indicator of self-group distancing more so than an indicator of disidentification (Becker & Tausch, 2014) or lack of group consciousness (Stout, Kretschmer, & Ruppanner, 2017). It is possible that compounding forms of self-group distancing-such as distancing one's (perceived)…”
Section: G Ener Al Discussionmentioning
confidence: 99%
“…How do the exchanges made by White families—exchanges that may be inapplicable or inaccessible to families of color—maintain systems of racial and class inequality? Stout, Kretschmer, and Ruppanner () recently reported that, for White and Latina women but not for Black women, marriage was associated with lower levels of identification with other women (“gender linked fate”) and, subsequently, a more conservative political ideology. Such findings beg for additional inquiries into the extent to which heterosexual marriage allows White women (and to a lesser extent Latina women) to capitalize on and align with (White) male privilege at the expense of Black women, thereby perpetuating race and class advantage.…”
Section: Moving Forward: Implications and Avenues For Social Exchangementioning
confidence: 99%